Plugging Gaps in Payment Systems: Evidence from the Take-Up of New Medicare Billing Codes - Jeffrey P. Clemens; Jonathan M. Leganza; Alex Masucci (Center for Economic Studies and ifo Institute (CESifo), 2021)
Over the last decade, the U.S. Medicare program has added new billing codes to enhance the financial rewards for Chronic Care Management and Transitional Care Management. We show that the take-up of these new billing codes is gradual and exhibits substantial variations across markets and physician groups, indicating that frictions to take-up may delay the impacts of payment reforms. We show that patterns of care and billing code substitution and complementarity can be important for assessing the costs and care access impacts of payment reforms. In our particular context, we estimate that the new Transitional Care Management codes had substantial impacts on the overall provision of evaluation and management services, flu vaccinations, and other recommended services, while the new Chronic Care Management codes did not. These patterns of complementarity shape both the costs and benefits of the introduction of these payment reforms, including the effects of the new billing codes on the overall return to specializing in primary care.
Keywords: H51; H57; I10; 330; health care; health economics; payment systems; procurement